Soft spinal gripper with enhanced electroadhesion function - Wang, Kai (Nanyang Technological University, 2023)
Soft robotics, materials science, and stretchable electronics are three fields that have seen significant advances in recent years. The development of soft grippers is one area where these fields have converged, leading to rapid progress in the design and development of flexible robotic grippers. This project focuses on the design and development of a soft spinal gripper using the principles of soft robotics. The gripper's nature, materials, and actuation method are all thoroughly discussed in this report, providing a deep insight into the design process. The tendon-driven actuation of the gripper is facilitated by an integrated circuit, which controls the motion of a stepper motor. The gripper mechanics were designed using 3D modelling, and the gripper finger was 3D printed using polymer resin. The bending test and pressure force test were conducted to analyse the structural and mechanical performance of the gripper. Additionally, an electroadhesion technique was used to extend the functionality of the gripper. Overall, this project demonstrates the potential of soft robotics for the development of flexible and versatile grippers that can be used in a range of applications.